ESTUDO SOBRE A OCORRÊNCIA DE ACIDENTES PELO USO DE PRODUTOS E SERVIÇOS NA POPULAÇÃO ASSISTIDA EM HOSPITAIS DE SÃO LUÍS-MA. - Dias, Líssia Maria de Souza (2008)
This study is about accidents arising from the use of products and services related from the consumers of São Luís-MA recorded at emergency hospitals. This is a cross-sectional descriptive study with a sample of 257 respondents aiming to detect the envelopment of products and services in accidents, profile the injured people as the age, the shift, the affected body segment, the kind of fall, local and work, as well as to detect the implication of the products and services in the incidents, describe the frequently injuries, indicate the main types of products and and services, by order on incidence, identify the features of accidents caused by falls, check gender and age join the type of the product na service, local, shift and body segment and kind of fall, and check the rate among gender and age with the factors associated to the accidents. From the results this can highlight that 57.6% were considered consumer incidents, 54.1% of the incidents the main victms are children, 58.4% are male, the body segments most affected were the upper and lower limbs 33.5%, 50.2% of the accidents ocurred at home, the most common injuries were contusions 49.0%, traumatic brain injury (TBI) and fractures 15.2%, the products with higher percentage were the vehicles 18.7%, the maintenance services corresponded to 8.6% and the afternoon shift was the predominant 44.7%.